Soupy saturdays - Blume, Judy; Pankhurst, Kate (Macmillan Children's London, 2009)
"Jake (the pain) and Abigail (the great one) are like any other brother and sister. They fight about anything and everything. Whether they are getting a haircut, learning to ride a bike, playing football, having a birthday party or even dog-sitting, they know exactly how to drive each other crazy!"--Back cover. Suggested level: primary